Delayed massive hemorrhage due to external iliac artery pseudo-aneurysm and uretero-iliac artery fistula following robotic radical cystectomy and intracorporeal Studer pouch reconstruction: endovascular management of an unusual complication - Atmaca, Ali Fuat; Canda, Abdullah Erdem; Gumus, Mehmet; Canyigit, Murat; Asil, Erem; Balbay, Mevlana Derya (Canadian Urological Association Journal, 2013)
We report a very unusual complication of uretero-iliac artery fistula that developed following robotic radical cystectomy (RARC), bilateral extended pelvic lymph node dissection and intracorporeal Studer pouch reconstruction. Our patient was a 54-year-old male who was admitted 1 month after undergoing robotic surgery due to intermittently occurring massive transurethral bleeding necessitating blood transfusion that stopped by itself. Angiography showed a right external iliacartery pseudo-aneurysm and a fistula tract between the pseudo-aneurysm and Wallace type ureteral anostomosis that was successfully treated by an angiographic endovascular stent insertion at this level. Uretero-iliac artery fistula might occur following RARC, bilateral extended pelvic lymph node dissection and intracorporeal Studer pouch reconstruction leading to intermittently massive transurethral bleeding. Angiography and stenting are important for diagnosis and successful treatment of this rare entity.